Policy and political consequences of mandatory climate impact assessments: an explorative study of German cities and municipalities. Issue 1 (2nd January 2021) - Rilling, Benedikt; Tosun, Jale
ABSTRACT: Since May 2019, several German cities and municipalities have declared a 'climate emergency', an action which makes climate impact assessments mandatory for all projects or policy proposals. How have the processes in the local governments changed in response to the emergency status? How have the processes in the city and municipal councils changed? And how, if at all, has the relationship between elected politicians (who make up the city and municipal councils) and bureaucrats (who make up the local government) changed? Based on 13 interviews carried out with representatives of city and municipal councils and local governments, we show, first, that local governments expect a higher workload and to spend more time on cross-sectoral coordination and cooperation. Second, the issue of climate change is now part of the political agenda in the local councils. Third, the administrative actors are now in a stronger position vis-à-vis the political ones as they can de facto veto projects or policies. Overall, we conclude that local-level climate politics has changed following the declaration of the emergency status; however, the design of the corresponding policies has not changed to reflect the cross-sectoral character of responses to climate change.